Ten micrometer pixel, quantum dots color conversion layer for high resolution and full color active matrix micro‐LED display. Issue 6 (24th April 2019) - Kim, Hyo‐Min; Ryu, Misun; Cha, James H.J.; Kim, Hyun Soo; Jeong, Tak; Jang, Jin
Abstract: A fine patternable quantum dots (QDs) color conversion layer (CCL) for high resolution and full color active matrix (AM) micro‐LED (μ‐LED) display is demonstrated. QDs CCL could be patterned until 10 μm using photolithography process. It is found that multicoatings with red and green QDs (R‐ and G‐QDs) CCLs on LED array can provide full color AM display. Abstract : A fine patternable quantum‐dots (QDs) color conversion layer (CCL) for high resolution and full color active matrix (AM) micro‐LED (μ‐LED) display is demonstrated. In this work, R‐ and green QDs (G‐QDs) CCL could be patterned until 10 μm using simple photolithography process on LED array for full color AM display.